The Merchant of Venice - Shakespeare, William, 1564-1616.; Merchant, W. Moelwyn (Cambridge ; New York : Cambridge University Press, Penguin Books, 1995)
An edition of Shakespeare's play, including discussion of its plot, characters, themes, language, production, and author.
Keywords: Young adult drama, English; Comedies